DCE-MRI assessment of response to neoadjuvant SABR in early stage breast cancer: Comparisons of single versus three fraction schemes and two different imaging time delays post-SABR. (March 2020) - Mouawad, Matthew; Biernaski, Heather; Brackstone, Muriel; Lock, Michael; Yaremko, Brian; Shmuilovich, Olga; Kornecki, Anat; Ben Nachum, Ilanit; Muscedere, Giulio; Lynn, Kalan; Prato, Frank S.; Thompson, R. Terry; et al.
Highlights: Early stage breast cancer patients were treated with 1 or 3 fraction SABR. Tumour and tissue changes were assessed using DCE-MRI at 1 or 3 weeks. Response at 1 week was confounded by acute inflammatory effects. 2.5 weeks post-SABR seems sufficiently long for tumour response assessment. Only 1 fraction SABR increased tissue enhancement, suggesting vascular damage. Abstract: Purpose: To determine the effect of dose fractionation and time delay post-neoadjuvant stereotactic ablative radiotherapy (SABR) on dynamic contrast-enhanced (DCE)-MRI parameters in early stage breast cancer patients. Materials and methods: DCE-MRI was acquired in 17 patients pre- and post-SABR. Five patients were imaged 6–7 days post-21 Gy/1fraction (group 1), six 16–19 days post-21 Gy/1fraction (group 2), and six 16–18 days post-30 Gy/3 fractions every other day (group 3). DCE-MRI scans were performed using half the clinical dose of contrast agent. Changes in the surrounding tissue were quantified using a signal-enhancement threshold metric that characterizes changes in signal-enhancement volume (SEV). Tumour response was quantified using K trans and ve (Tofts model) pre- and post-SABR. Significance was assessed using a Wilcoxin signed-rank test. Results: All group 1 and 4/6 group 2 patients' SEV increased post-SABR. All group 3 patients' SEV decreased. The mean K trans increased for group 1 by 76% (p = 0.043) while group 2 and 3 decreased 15% (p = 0.028) and 34% (p = 0.028), respectively. For ve, there was no significant change in Group 1 (p = 0.35). Groups 2 showed an increase of 24% (p = 0.043), and Group 3 trended toward an increase (23%, p = 0.08). Conclusion: Kinetic parameters measured 2.5 weeks post-SABR in both single fraction and three fraction groups were indicative of response but only the single fraction protocol led to enhancement in the surrounding tissue. Our results also suggest that DCE-MRI one-week post-SABR may be too early for response assessment, at least for single fraction SABR, whereas 2.5 weeks appears sufficiently long to minimize confounding acute effects.